The effect of methoxyflavone on P-glycoprotein-mediated transport and intracellular reactive oxygen species in cancer cells - Keeddee J. (2014)
The natural products have been reported to exhibit anticancer and antioxidant activities. The aim of this study was to determine the effect of 5,4′-dihydroxy-3,6,7,8-tetramethoxyflavone (WP279), 5,5′-dihydroxy- 6,7,3′,4′-tetramethoxyflavone (WP280) and 5,3′-dihydroxy-3,6, 7,8,4′-pentamethoxyflavone(WP283) on P-glycoprotein-mediated transport and intracellular reactive oxygen species in K562 and K562/adr (P-glycoprotein overexpression) cancer cells. The ability to inhibit of P-glycoprotein-mediated transport of pirarubicin out of the cells was determined using non-invasive functional spectrofluorometric techniuqe. The ratio of ka1/ka0 value was used to indicate the ability of molecule to inhibit the P-glycoprotein active efflux of a drug that if k a1/ka0 = 1 or 0, these mean that there was not inhibition and was completely blocked P-glycoprotein function respectively. The three methoxyflavones could partially inhibit function of P-glycoprotein active efflux of a drug by ka1/k a0 values equal to 0.3-0.1 approximately. For the effect of three methoxyflavones on intracellular reactive - oxygen species in both cancer cells was also determined by using 2′,7′-dichlorofluorescein diacetate as a fluorescent probe. The involved parameters in dichlorofluorescein formation, k2ROS1 could be quantitatively determined by fitting mathematically equation to the experimental spectrofluorometric data. WP279 WP280 and WP283 could deplete k2ROS1, in K562 cells by about 53%, 55% 38% and K562/adr cells by 54%, 67%, and 58%, respectively. The three methoxyflavones decreased in intracellular reactive oxygen species in both cancer cells as a concentration dependent manner.